Freezing Temperature Field of FSPR under Different Pipe Configurations: A Case Study in Gongbei Tunnel, China - Yin Duan; Chuanxin Rong; Hua Cheng; Haibing Cai; Wei Long (Advances in Civil Engineering)
As a new tunnel presupport construction technology, the freeze-sealing pipe roof method (FSPR) has been successfully applied to the Gongbei Tunnel Project for the first time in China. To overcome the practical difficulties of this new method in the freezing construction process, such as welding difficulties of the profiled freezing tube, refrigerant leakage, and long construction period, based on the principle of an equal cooling capacity, an improved design of freezing tube was proposed. By designing three different pipe configurations and using scaled model tests and numerical simulation, the feasibility of the improvement and the difference in the freezing temperature field were studied. The research results show that the improved design with double circular freezing tubes exhibited a lower temperature and a higher cooling rate during the test, and the time required to meet the freezing design requirements was significantly shortened. Finally, a composite structure of “pipe roof and frozen soil curtain” with a better carrying capacity and water sealing performance was formed. It was recommended to strengthen the temperature monitoring at the pipe wall in the preliminary stage of the freezing construction to ensure the water sealing effect between the pipes. In the later stage, attention should be paid to monitoring the thickness of the frozen curtain and reducing excessive frost heave through technical means such as cooling capacity control. The improvement and configurations proposed in this research could effectively replace profiled freezing tubes in the original project, better adapt to horizontal freezing projects of similar curved tunnels, achieve the freezing goal faster, and provide a reference for the promotion of the FSPR.